The Role of Strategic audit in detection of financial corruption cases in Iraq - Proposed Framework - علي سلامة ابراهيم (Journal of Economics and Administrative Sciences, 2017)
This research focuses on detecting the financial corruption cases in Iraq in light of adoption the strategic audit, the paper deals with the problem of the proliferation corruption cases particularly financial in Iraq and dramatically in the presence of audit and control devices as well as inspection and integrity devices, which indicates the existence of deficiencies and weaknesses in those devices in the implementation of audit and control functions in order to detect the corruption cases in the economic units in Iraq. Stems objective of this research through the provision of approach of strategic audit concepts and indicate the extent importance of adopting of strategic audit as a means to detect the financial corruption cases in the Iraqi environment as well as a framework proposal for strategic audit can be applied in the local environment in order to detecting the financial corruption cases and ways to treated them. The research found a number of conclusions was that the most important results of the empirical studies that measure the effectiveness of the control systems of internal and external both types as well as the Integrity Commission and the departments of inspectors general have proven that the actions taken by those actors is insufficient and ineffective to limit the financial corruption cases in Iraq. The research was presented several recommendations were the most important of the need to adopt a framework proposed strategic audit and in earnest, which would help financial control bodies and the Integrity Commission and the departments of inspectors general in the performance of its role effectively in order to detect the financial corruption cases in the economic units operating in the Iraqi environment, and to be completed of strategic audit to the fullest requires that have a logical sequential steps to give positive results.